Measuring relative efficiency of secondary education in selected EU and OECD countries: the case of Slovenia and Croatia - Aristovnik, Aleksander; Obadić, Alka (Technological and Economic Development of Economy, 2014)
This article continues on a number of previous studies by other scientists in investigating secondary education efficiency by applying a non-parametric methodology. In this respect, the purpose of the article is to review some previous studies on measuring the efficiency of public (secondary) education sector as well as some conceptual and methodological issues of a non-parametric approach. Most importantly, the Data Envelopment Analysis (DEA) technique is presented and then applied to a wide range of EU and OECD countries, including Slovenia and Croatia, to evaluate the technical efficiency of secondary education. The empirical results show that technical efficiency in secondary education varies significantly across the great majority of EU and OECD countries. Both Slovenia and Croatia show a relatively high level of technical inefficiency in their secondary education as they respectively only rank in the third and fourth quartiles among selected countries. Therefore, rationalising public secondary education spending is strongly recommended with possible redirecting of some excessive resources to the tertiary education sector.First published online: 11 Aug 2014